Description of the Human Penile Urethra Epithelium - Matisse Duval; David Brownell; Stéphane Chabaud; Alexis Laungani; Eric Philippe; Stéphane Bolduc (Medicina)
Background and Objectives: The male urethra is a complex structure that plays a critical role in genitourinary health and function. Despite its importance, histological descriptions of the penile urethra, particularly its epithelial components, remain incomplete. This study offers a comprehensive histological analysis of the penile urethra, focusing on the epithelium across distinct anatomical regions, including the glans, distal and proximal fossa navicularis and spongy urethra. Materials and Methods: Utilizing five human penile specimens, we employed various staining techniques to elucidate the structural characteristics of these epithelial tissues. Results: Our findings reveal notable variations in epithelial composition, such as the presence of glycogen-rich cells in the distal fossa navicularis and the presence of mucous glands in the spongy urethra and proximal fossa navicularis. Additionally, we identified a previously underreported valvule-like structure in the distal fossa navicularis in two of the specimens. In addition, the epithelium of the glans and the distal fossa navicularis are thicker than the ones of the proximal fossa navicularis and the spongy urethra. With a similar vascular density, the orientation of the blood vessels also diverges starting with the distal fossa navicularis. Conclusions: This study provides new insights into the histological organization of the penile urethra, offering critical reference data that can enhance our understanding of urethral pathologies and improve the outcomes of surgical interventions, particularly in the context of tissue engineering and reconstructive surgery.